Richard Kearney's anatheistic wager : philosophy, theology, poetics - Doude van Troostwijk, Chris, 1962-; Clemente, Matthew, 1989- (Indiana series in the philosophy of religion., 2018)
Philosopher Blaise Pascal famously insisted that it was better to wager belief in God than to risk eternal damnation. More recently, Richard Kearney has offered a wager of his own'the anatheistic wager, or return to God after the death of God. In this volume, an international group of contributors consider what Kearney's spiritual wager means. They question what is at stake with such a wager and what anatheism demands of the self and of others. The essays explore the dynamics of religious anatheistic performativity, its demarcations and limits, and its motives. A recent interview with Kearney focuses on crucial questions about philosophy, theology, and religious commitment. As a whole, this volume interprets and challenges Kearney's philosophy of religion and its radical impact on contemporary views of God.